2023
DOI: 10.2147/jir.s385977
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Ferroptosis in Various Chronic Liver Diseases: Opportunity or Challenge

Abstract: Ferroptosis is a recently identified iron-dependent form of intracellular lipid peroxide accumulation-mediated cell death. Different from other types of cell death mechanisms, it exhibits distinct biological and morphological features characterized by the loss of lipid peroxidase repair activity caused by glutathione peroxidase 4, the presence of redox-active iron, and the oxidation of phospholipids-containing polyunsaturated fatty acids. In recent years, studies have shown that ferroptosis plays a key role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…During the review and revision process of this work, lots of groups have published their experimental studies via the arXiv preprint server. It is worth noticing that almost all the electrical transport studies are consistent with our major resultsemiconductor/insulator-like transport behavior for the nominal Pb 10−x Cu x (PO 4 ) 6 O compound sintered from Pb 2 SO 5 and Cu 3 P. Specifically, in the study by Hou et al, [15] most of their samples exhibit semiconducting behavior, except that one piece of small samples exhibits extraordinarily small metallic resistance; in the experiment study by Guo et al, [16] the temperature-dependent resistivity of their Pb 10−x Cu x (PO 4 ) 6 O pellet sample shows semiconducting transport behavior similar to ours; in the report by Kumar et al, [17] it was mentioned that their samples are highly resistive; Timokhin et al [18] reported that their samples have strong inhomogeneity and are resistive with largely varied transport properties; Zhu et al [19] presented the semiconducting transport behavior for the Pb 10−x Cu x (PO 4 ) 6 O major phase; Zhang et al [20] reported the insulating transport behavior with a logarithmic temperature dependence of resistivity; Singh et al [21] reported the insulating nature of the temperature-dependent resistivity; the major phase of the Pb 10−x Cu x (PO 4 ) 6 O compound fabricated by Wu et al [22] exhibits the semiconducting transport behavior; and Wang et al [29] found that all their samples are semiconducting/insulating no matter whether the samples show magnetic levitation or not.…”
Section: Discussion and Summarysupporting
confidence: 71%
See 1 more Smart Citation
“…During the review and revision process of this work, lots of groups have published their experimental studies via the arXiv preprint server. It is worth noticing that almost all the electrical transport studies are consistent with our major resultsemiconductor/insulator-like transport behavior for the nominal Pb 10−x Cu x (PO 4 ) 6 O compound sintered from Pb 2 SO 5 and Cu 3 P. Specifically, in the study by Hou et al, [15] most of their samples exhibit semiconducting behavior, except that one piece of small samples exhibits extraordinarily small metallic resistance; in the experiment study by Guo et al, [16] the temperature-dependent resistivity of their Pb 10−x Cu x (PO 4 ) 6 O pellet sample shows semiconducting transport behavior similar to ours; in the report by Kumar et al, [17] it was mentioned that their samples are highly resistive; Timokhin et al [18] reported that their samples have strong inhomogeneity and are resistive with largely varied transport properties; Zhu et al [19] presented the semiconducting transport behavior for the Pb 10−x Cu x (PO 4 ) 6 O major phase; Zhang et al [20] reported the insulating transport behavior with a logarithmic temperature dependence of resistivity; Singh et al [21] reported the insulating nature of the temperature-dependent resistivity; the major phase of the Pb 10−x Cu x (PO 4 ) 6 O compound fabricated by Wu et al [22] exhibits the semiconducting transport behavior; and Wang et al [29] found that all their samples are semiconducting/insulating no matter whether the samples show magnetic levitation or not.…”
Section: Discussion and Summarysupporting
confidence: 71%
“…An impressive aspect that might be highly relevant to the resistance transition in the previously reported data by Lee et al, [3,4] is Cu 2 S. It was pointed out [19,23] that as early as in 1951, [24] the electrical transport properties of Cu 2 S were found to exhibit a sharp first-order resistive transition at ≈380 K, and correspondingly, the specific heat peaks [23] at this temperature too (Note: the possible magnetic-field response of the first-order resistive transition in Cu 2 S, which has been implied by the magnetotransport data collected by Wu et al, [22] might be promising for exploring novel magnetoelectronic phenomena and constructing useful magnetoelectronic devices [6][7][8][9][10][11][12][30][31][32] ). Another important aspect is the recently synthesized single crystals of Pb 10−x Cu x (PO 4 ) 6 O seem kind of transparent, [25,26] which implies that they might be intrinsically highly insulating although de-Figure 13.…”
Section: Discussion and Summarymentioning
confidence: 83%
“…In the present study, a significant reduction in GPX4, SLC7A11, and GSH levels in vulnerable plaques was also demonstrated, suggesting that a higher degree of ferroptosis progression was occurring in vulnerable plaques. GPX4 is the major phospholipid hydroperoxide (PLOOH)-neutralizing enzyme and it is involved in ferroptosis induced by erastin/RSL3 (27). The GSH pathway has been identified as a key antioxidant defense pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive iron accumulation and the inhibition of glutathione peroxidase 4 trigger ferroptosis, which causes cell plasma membrane rupture[ 23 ]. Accumulating research studies have demonstrated that ferroptosis is involved in different liver diseases, including alcoholic liver disease, NASH, cirrhosis, and cancer[ 24 , 25 ]. Several molecular signaling pathways are involved in ferroptosis in liver diseases, such as the nuclear factor erythroid 2-related factor 2[ 26 ], heat shock protein family A member 8[ 27 ], and nuclear receptor coactivator 4[ 28 ].…”
Section: Initiation Of Liver Fibrosis: Cellular and Molecular Mechanismsmentioning
confidence: 99%